The Influence of Work Motivation and Job Satisfaction on Wadesa Restaurant's Organizational Commitment - Sunu, Putu Rendra Pryandhika; Ramacandra, I Gusti Ngurah Sadana (PT. Global World Scientific, 2023)
This study aims to analyze the effect of work motivation and job satisfaction on organizational commitment at Wadesa Restaurant. The method used is a quantitative approach with a causal associative design to test the relationship between independent variables, namely work motivation (X1) and job satisfaction (X2), on the dependent variable, namely organizational commitment (Y). The sample in this study included all employees of Wadesa Restaurant totaling 45 people, with a saturated sampling technique to obtain more accurate data. Data were collected through observation, distributing questionnaires using a five-point Likert scale, and company documentation. The analysis technique used was multiple linear regression with the classical assumption test, F test, and t test to test the significance of the influence of each variable. The results of the study indicate that job satisfaction has a more dominant and significant influence on organizational commitment compared to work motivation. The regression model used meets the classical assumptions, with an R Square value of 0.671, indicating that 67.1% of the variability in organizational commitment can be explained by work motivation and job satisfaction. However, work motivation does not show a significant influence in this model. The implications of these findings emphasize the importance of organizational policies that increase job satisfaction, such as performance rewards, career development opportunities, and work-life balance. With a more conducive work environment, it is expected that employee organizational commitment can increase, which ultimately contributes to the company's performance and sustainability.